Effectiveness study of foliar nutrient on growth and production of okra (Abelmoschus esculentus L.) - Mohammad Ashshabru Syakirin Kamsol.
The world population has increased from the past decades. This lead to a highdemand for food with the limited agricultural land. The use of more chemicalfertilizer and pesticides is certainly not a solution as the limited resource and thus forcing farmers to produce a healthy and environmentally safe food in a sustainable way. Therefore, this experiment is conducted to test either the foliar nutrient fertilizer may increase the yield and eventually substitute the common solid fertilizer used in farming system. The objective of this study is to evaluate the efficiency of foliar nutrient fertilizer on the growth and yield performance of Abelmoschus Esculentus L. This experiment hypothesize that the foliar nutrient fertilizer application can enhance the growth and yield of okra. The experiment was conducted in Ladang 10, UPM, Serdang, Selangor and laid out as Randomized Completely Block Design (RCBD) with 4 treatments and 6 replications. Treatments applied consist of T1 :Foliar fertilizer (HerbaGreen) alone, T2 : Chemical fertilizer (NPK 15:15:15), T3 : Chemical fertilizer (NPK 15:15:15) + foliar (HerbaGreen) and T4 : Control (without fertilizer). The treatments from foliar were applied by spraying 2% of HerbaGreen at the leaf of the plant every 2 weeks and the chemical fertilizers were evenly spread round the crop based on the recommendation from Department of Agriculture Malaysia. The data were by measuring the plant height (every 4 weeks interval), measuring weight of yield (until 120 DAP), counting days to flowering (from 1DAP), counting number of fruits and branches per plant (until 120 DAP). Soil analyses were conducted before and after the experiment to compare the soil physical and chemical properties. All the parameters measured were analyzed for ANOVO and mean separations of LSD test text using SAS 9.0 or later at p<0.05 and the results obtained were discussed. Treatment 3, T3 was the highest in the result of the growth rate and yield production parameter as compared to other treatments. There was significant different between Treatment 1, T1 and treatment 2, T2 where T2 showed prominent results then T1. Therefore, concluded that foliar nutrient fertilizer (HerbaGreen) cannot substitute the common chemical fertilizer (BPK).